Sclerostin and Its Associations With Bone Metabolism Markers and Sex Hormones in Healthy Community-Dwelling Elderly Individuals and Adolescents - Xu, Yang; Gao, Chao; He, Jinwei; Gu, Wenqin; Yi, Chuntao; Chen, Bihua; Wang, Qingqing; Tang, Feng; Xu, Juliang; Yue, Hua; Zhang, Zhenlin (Frontiers in Cell and Developmental Biology, 2020)
Sclerostin is an important regulator of bone mass involving Wnt/β-catenin signaling pathway. We aimed to obtain the profile of serum sclerostin level and explore its associations with bone metabolism markers and sex hormones in healthy community-dwelling Chinese elderly individuals and adolescents. A cross-sectional study was performed in three communities in Shanghai. In all, 861 participants, including 574 healthy elderly individuals and 287 healthy adolescents, were recruited. The levels of serum sclerostin, procollagen type 1 N-terminal propeptide (P1NP), β-CrossLaps of type I collagen containing cross-linked C-telopeptide (β-CTX), parathyroid hormone (PTH), 25-hydroxyvitamin D [25(OH)D], estradiol (E2), testosterone (T) and sex hormone-binding globulin (SHBG) were measured in blood samples from all participants. Median sclerostin level was higher in males than in females and in elderly individuals than in adolescents (elderly males: 54.89 pmol/L, elderly females: 39.95 pmol/L, adolescent males: 36.58 pmol/L, adolescent females: 27.06 pmol/L； both P<0.05). In elderly individuals, serum sclerostin was positively correlated with age (β=0.176, P<0.001) and T (β=0.248, P=0.001), but negatively associated to P1NP (β=-0.140, P=0.001). In adolescents, circulating sclerostin was significantly and positively associated with P1NP (β=0.192, P=0.003). The directions of the association between sclerostin and P1NP were opposite in Chinese elderly individuals and adolescents, which may reflect that sclerostin plays distinct roles in different functional states of the skeleton. Our findings revealed the rough profile of circulating sclerostin level in general healthy Chinese population and its associations with bone metablism markers and sex hormones, which may provide a clue to further elucidate the cross action of sclerostin in bone metabolism and sexual development.